2022
DOI: 10.1177/00111287221098580
|View full text |Cite
|
Sign up to set email alerts
|

Fear Among the Feared: Arab Americans’ Fear of Crime in an Ethnic Enclave Community

Abstract: Drawing on racial threat hypothesis and in-depth interviews with first- and second-generation Arab immigrants, this study explores Arab immigrants’ perceptions of risk and fear of crime in an ethnic enclave community. We find that Arab immigrants’ fear of crime is shaped by the unique context in which they live, with this particular population perceiving members of other minority groups as the greatest threat to their culture, community, and safety. This study extends the minority threat perspective, which typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Meanwhile, the effect of perceived disorder on cooperation may be less strong among Arab than non-Arab Americans. A recent qualitative study (Zaatut and Jacobsen, 2022) found that Arab Americans' perception of victimization risk was not impacted by the presence of crime and disorder in and around their neighborhood, countering the commonly found linkage between disorder and fear of crime in the general population (Gibson et al, 2002). This overall feeling of safety despite signs of disorder may come from the strong sense of community Arab immigrants felt inside their ethnic enclave (Zaatut and Jacobsen, 2022).…”
Section: The Moderating Effect Of Ethnicity On Neighborhood Context -...mentioning
confidence: 96%
See 1 more Smart Citation
“…Meanwhile, the effect of perceived disorder on cooperation may be less strong among Arab than non-Arab Americans. A recent qualitative study (Zaatut and Jacobsen, 2022) found that Arab Americans' perception of victimization risk was not impacted by the presence of crime and disorder in and around their neighborhood, countering the commonly found linkage between disorder and fear of crime in the general population (Gibson et al, 2002). This overall feeling of safety despite signs of disorder may come from the strong sense of community Arab immigrants felt inside their ethnic enclave (Zaatut and Jacobsen, 2022).…”
Section: The Moderating Effect Of Ethnicity On Neighborhood Context -...mentioning
confidence: 96%
“…A recent qualitative study (Zaatut and Jacobsen, 2022) found that Arab Americans' perception of victimization risk was not impacted by the presence of crime and disorder in and around their neighborhood, countering the commonly found linkage between disorder and fear of crime in the general population (Gibson et al, 2002). This overall feeling of safety despite signs of disorder may come from the strong sense of community Arab immigrants felt inside their ethnic enclave (Zaatut and Jacobsen, 2022). If Arab American residents are less sensitive to the disorder conditions of their neighborhood, then the direct and indirect effect of perceived disorder on cooperation may be less evident as well.…”
Section: The Moderating Effect Of Ethnicity On Neighborhood Context -...mentioning
confidence: 99%
“…Wu et al (2017) find higher levels of fear of both general crime and prejudice related crime among Arab Americans than non-Arab Americans. Similarly, a review of studies of immigrants, including Koreans, Ghanaians, and those who do not speak English well, finds that being more isolated and less acculturated increases fear of bias crime (Zaatut & Jacobsen, 2023).…”
Section: Key Theoretical Perspectives and Correlates Of Fear Of Crimementioning
confidence: 99%